Positive airway pressure delivery: overcoming old hurdles, exploring new frontiers - Messineo, Ludovico; White, David P.; Noah, William H. (Frontiers in Sleep, 2024)
Despite being the gold-standard treatment for obstructive sleep apnea (OSA), continuous positive airway pressure (CPAP) faces important challenges, particularly with patient adherence. Many individuals find CPAP difficult to tolerate due to noise, social inconveniences, characteristics inherently linked to their sleep disorder and side effects, including mask discomfort, air leaks, nasal congestion, and the unnatural sensation of exhaling against positive pressure. All this often leads to reduced usage, limiting CPAP's potential to deliver long-term health benefits. This review revisits the dynamics of pharyngeal collapse during sleep on PAP, offering a new interpretation that challenges the long-standing view that higher inspiratory pressure is required to maintain pharyngeal patency. Emerging evidence, combined with the knowledge from older studies, suggests that airway collapse often occurs near end-expiration, which may be the only time that substantial positive airway pressure is required. Efforts to improve CPAP compliance have reduced expiratory pressure, leading to the introduction of bilevel PAP (BPAP) and expiratory pressure relief algorithms, which may cause airway destabilization, without yielding the improvements in adherence that were initially anticipated. Thus, despite over three decades of innovation, which have also seen heated humidifiers and tubes, customized 3D-printed masks and auto-titrating PAP come to market, there has been limited success in systematically increasing long-term CPAP adherence rates. In response, we discuss novel approaches such as V.-Com® and KairosPAP™ (KPAP™), which reduce inspiratory pressure and, in the case of KPAP™, also much of expiratory pressure, returning to full pressure only at the end of expiration. Recent studies suggest these technologies improve comfort and reduce unintentional leaks and may lead to better adherence without sacrificing treatment effectiveness. This aligns with the hypothesis that stabilizing the airway during end-expiration may be key to enhancing CPAP comfort and adherence. In conclusion, while technological advancements have improved the CPAP experience, further progress will likely come from solutions that better address patient comfort with the applied pressure. KPAP™ is one such innovation with the potential to enhance adherence, but additional research is needed to fully understand its long-term impact and effectiveness in PAP therapy for OSA.